Предмет: Алгебра,
автор: Аноним
(х-2)(х-3)=0 *
1 балл
Ответы
Автор ответа:
0
Объяснение:
(x-2)(x-3)=0
Решением является совокупность:
(x-2)=0 (1)
(x-3)=0 (2)
(1)
(x-2)=0
x=2
(2)
(x-3)=0
x=3
Ответ: x1=2 x2=3
Автор ответа:
0
(х-2)(х-3)=0 ⇔ [ x -2 =0 ; x-3 =0. ⇔ [ x =2 ; x=3 . ⇒ Ура ! финиш
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Английский язык,
автор: Аноним
Предмет: Другие предметы,
автор: ladykoch
Предмет: Математика,
автор: умный264
Предмет: История,
автор: Викторрия154